2023
DOI: 10.1093/plphys/kiad370
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANS interacts with and antagonizes ABF transcription factors during salt stress under long-day conditions

Abstract: CONSTANS (CO) is a critical regulator of flowering that combines photoperiodic and circadian signals in Arabidopsis (Arabidopsis thaliana). CO is expressed in multiple tissues, including seedling roots and young leaves. However, the roles and underlying mechanisms of CO in modulating physiological processes outside of flowering remain obscure. Here, we show that the expression of CO responds to salinity treatment. CO negatively mediated salinity tolerance under long-day (LD) conditions. Seedlings from co mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…Whether this model of interplay between ABFs and NF-YA/B/C/NF-YCO/B/C can be applied to the FT promoter regulation is unclear. Intriguingly, recent data support the physical interaction between CO and ABF1/2/3/4 and their antagonistic roles at salinity-responsive genes promoters (Du et al, 2023). The ABFs do not, however, display binding to the FT chromatin region (Song et al, 2016;Hwang et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Whether this model of interplay between ABFs and NF-YA/B/C/NF-YCO/B/C can be applied to the FT promoter regulation is unclear. Intriguingly, recent data support the physical interaction between CO and ABF1/2/3/4 and their antagonistic roles at salinity-responsive genes promoters (Du et al, 2023). The ABFs do not, however, display binding to the FT chromatin region (Song et al, 2016;Hwang et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…This gene is homologous to Arabidopsis thaliana AT1G45249 (Supplementary Table 4 ). In Arabidopsis, this gene encodes abscisic acid response element binding Factor 2, and several studies have reported that this gene is responsive to salt stress [ 122 ] and drought tolerance [ 123 ]. These results reveal the important role of transcription factors in the response to ABA and drought stress in sunflowers.…”
Section: Discussionmentioning
confidence: 99%
“…In model plant Arabidopsis, AtCOL4 participates in ABA pathway and salt-stress responses through an ABA-dependent signaling pathway to positively regulate non-biological stress tolerance [149]. Conversely, AtCO negatively mediates salt tolerance in Arabidopsis by interacting with four ABSCISIC ACID-RESPONSIVE ELEMENT BINDING FACTORS (ABF1, ABF2, ABF3, and ABF4) [150]. Additionally, CO is also a JAZ-binding factor that participates in jasmonic acid signal transduction through protein interactions In model plant Arabidopsis, AtCOL4 participates in ABA pathway and salt-stress responses through an ABA-dependent signaling pathway to positively regulate nonbiological stress tolerance [149].…”
Section: Col Participates In Abiotic Stress Responsementioning
confidence: 99%
“…Additionally, CO is also a JAZ-binding factor that participates in jasmonic acid signal transduction through protein interactions In model plant Arabidopsis, AtCOL4 participates in ABA pathway and salt-stress responses through an ABA-dependent signaling pathway to positively regulate nonbiological stress tolerance [149]. Conversely, AtCO negatively mediates salt tolerance in Arabidopsis by interacting with four ABSCISIC ACID-RESPONSIVE ELEMENT BINDING FACTORS (ABF1, ABF2, ABF3, and ABF4) [150]. Additionally, CO is also a JAZ-binding factor that participates in jasmonic acid signal transduction through protein interactions [151].…”
Section: Col Participates In Abiotic Stress Responsementioning
confidence: 99%